Research Example for Business Students: Analysis of the Number of Passengers Departing on Domestic and International Flights at 4 Main Indonesian Airports in 2014-2018 - Pujiono Eddy (First Ciera Publisher, 2023)
This study aims to analyze the number of passengers departing on domestic flights and international flights at 4 main Indonesian airports in 2014-2018. This study also aims to provide simple examples of research to students in faculties and/or business majors, so that student research becomes more varied. This study used a hypothesis test of the proportion of 2 samples with a 5% alpha confidence level. Test-of-difference analysis is also used to make the research more comprehensive. Then the analysis continued with descriptive analysis. Based on data on the number of passengers on domestic and international flights, it can be analyzed with the result that there are differences in the number of passengers between domestic and international flights. This research can be the basis for further in-depth research on the factors that affect the number of passengers at certain airports. Further research can identify other aspects that can influence passenger decisions in choosing airports and flight routes, such as ticket prices, service quality, and consumer preferences. This research can also be developed using other statistical tools such as ANOVA or other statistical test tools.